Impact of Brachial-Ankle Pulse Wave Velocity on Myocardial Work by Non-invasive Left Ventricular Pressure-Strain in Non-hypertensive and Hypertensive Patients With Preserved Left Ventricular Ejection Fraction - Duan, Qin; Zhang, Dongying; Dong, Qian; Liao, Kangla; Yang, Yunjin; Ye, Liu; Ge, Ping; Qin, Shu (Frontiers in Cardiovascular Medicine, 2022)
Objective: Data regarding the influence of arterial stiffness on myocardial work(MW) has been scared. This study was performed to investigate the association between brachial-ankle pulse wave velocity (baPWV) and MW by non-invasive left ventricular pressure–strain in a population of normotensive and hypertensive individuals. Methods: Two hundred and eight participants (104 hypertensive and 104 normotensive individuals) were prospectively enrolled into the study. All participants underwent conventional echocardiography, as well as 2D speckle-tracking echocardiography to assess MW by non-invasive left ventricular pressure–strain and global longitudinal strain (GLS). baPWV measurements were made at the same day of echocardiography. Then participants were categorized according to baPWV tertiles. Correlation between baPWV and MW were analyzed. Predicting ability of baPWV for abnormal WM was analyzed using receiver operating characteristic (ROC) curve. Results:The median baPWV from low to high tertile group were 1286.5(1197.5-1343.5) cm/s, 1490.0 (1444.5-1544.0) cm/s and 1803.8(1708.3-1972.0) cm/s, respectively. In simple linear regression analysis, baPWV had a significant positive association with global work index (GWI), global constructed work (GCW), global wasted work (GWW) and a negative association with global work efficiency (GWE). The association remained significant after adjusted major confounding factors in multiple linear regression analysis. The area under ROC curve of baPWV for predicting abnormal GWI, GCW, GWW and GWE were 0.653, 0.666, 0.725 and 0.688, respectively (all p < 0.05). Conclusions: baPWV is significantly associated with all 4 components of MV using non-invasive left ventricular pressure-strain method in a mixed population of normotensive and hypertensive individuals.